2013
DOI: 10.1186/2051-4190-23-3
|View full text |Cite
|
Sign up to set email alerts
|

The nature of human sperm head vacuoles: a systematic literature review

Abstract: Motile sperm organelle morphology examination (MSOME) involves the use of differential interference contrast microscopy (also called Nomarski contrast) at high magnification (at least 6300x) to improve the observation of live human spermatozoa. In fact, this technique evidences sperm head vacuoles that are not necessarily seen at lower magnifications - particularly if the vacuoles are small (i.e. occupying <4% of the sperm head’s area). However, a decade after MSOME's introduction, it is still not clear whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Interactome approach also identifies proteins involved in chromatin regulation as potential SPANX-A/D interactors such as several histones (testis-specific H1 histone (H1FNT) and histone 1 (HISTH1T)) and chromatin regulators (SET domain-containing protein 9 (SETD9) and histone deacetylase 11 (HADC11)). This is consistent with the fact that SPANX-A/D protein family is present inside nuclear vacuoles, which have been widely associated with chromatin condensation failure and genomic instability [18][19][20] ,. Therefore, our results indicate that SPANX-A/D might play an important role in sperm physiology by regulating chromatin organisation in mature spermatozoa.…”
Section: Discussionsupporting
confidence: 87%
“…Interactome approach also identifies proteins involved in chromatin regulation as potential SPANX-A/D interactors such as several histones (testis-specific H1 histone (H1FNT) and histone 1 (HISTH1T)) and chromatin regulators (SET domain-containing protein 9 (SETD9) and histone deacetylase 11 (HADC11)). This is consistent with the fact that SPANX-A/D protein family is present inside nuclear vacuoles, which have been widely associated with chromatin condensation failure and genomic instability [18][19][20] ,. Therefore, our results indicate that SPANX-A/D might play an important role in sperm physiology by regulating chromatin organisation in mature spermatozoa.…”
Section: Discussionsupporting
confidence: 87%
“…A late paternal effect happening after this period could affect embryonic developmental arrest or may cause early abortions. Defected spermatozoa can lose early embryonic development through some mechanisms, containing fertilisation failure, embryo fragmentation or developmental arrest at the second pronuclear stage (Boitrelle et al, ). Garolla et al (, ) confirmed that spermatozoon with vacuoles was associated with a higher rate of DNA fragmentation, loosely packaged chromatin and abnormal chromosomes and sperm selection by MSOME can decrease the percentage of DNA fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…As we recently reported in a review article [ 19 ], the relationship between the presence of vacuoles and the degree of sperm chromatin condensation has been extensively studied (for an overview, see Table 13.1 (reproduced from [ 19 ])). Some researchers have focused on chromatin condensation in spermatozoa with large vacuoles.…”
Section: The Relationship Between Sperm Head Vacuoles and Sperm Chrommentioning
confidence: 96%
“…P values in bold type are statistically signifi cant. Table from [ 19 ], an Open Access article distributed under the terms of the Creative Commons Attribution License ( http://creativecommons.org/licenses/by/2.0 ), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited Firstly, in Cassuto et al's study of 26 patients, spermatozoa with an abnormally shaped head (i.e., an abnormal base and/or an asymmetric nuclear extrusion) and at least one large vacuole (although the size was not specifi ed) were selected under high magnifi cation [ 20 ]. This type of spermatozoa was referred to as "score-0."…”
Section: The Relationship Between Sperm Head Vacuoles and Sperm Chrommentioning
confidence: 96%
See 1 more Smart Citation